Linear kinematic analysis of cinematic biomechanics in semisquat knee flexion: a case study - Dan Alexandru SZABO; Nicolae NEAGU; Andreea ILIEȘ; Mariana ARDELEAN (Editura Universităţii din Oradea, 2021)
The study emphasized the necessity of kinesiology and biomechanical movement analysis in today's physical education, kinesiotherapy, and sports. Our experiment observed a biomechanical motion configuration of semi-squat knee flexion, vertical position, angle, speed, and acceleration. The Kinovea software, version 0.9.3, is utilized as a study tool for biomechanical investigation employing some specific kinesiological characteristics of the movement. The findings of the biomechanical action emphasized the unique semi-squat knee flexion and extension, displaying the complete action from a certain linear angle, angular velocity, and acceleration.